The globular cluster system mass-halo mass relation in the E-MOSAICS simulations - Bastian, Nate; Pfeffer, Joel; Kruijssen, Diederik; Crain, Robert A.; Trujillo-Gomez, Sebastian; Reina-Campos, Marta (Monthly notices of the Royal Astronomical Society, 2020)
Linking globular clusters (GCs) to the assembly of their host galaxies is an overarching goal in GC studies. The inference of tight scaling relations between GC system properties and the mass of both the stellar and dark halo components of their host galaxies are indicative of an intimate physical connection, yet have also raised fundamental questions about how and when GCs form. Specifically, the inferred correlation between the mass of a GC system (MGC) and the dark matter halo mass (Mhalo) of a galaxy has been posited as a consequence of a causal relation between the formation of dark matter mini-haloes and GC formation during the early epochs of galaxy assembly. We present the first results from a new simulation of a cosmological volume (L = 34.4 cMpc on a side) from the E-MOSAICS suite, which includes treatments of the formation and evolution of GCs within the framework of a detailed galaxy formation model. The simulated MGC-Mhalo relation is linear for halo masses >5 × 1011 M⊙, and is driven by the hierarchical assembly of galaxies. Below this halo mass, the simulated relation features a downturn, which we show is consistent with observations, and is driven by the underlying stellar mass-halo mass relation of galaxies. Our fiducial model reproduces the observed MGC-M⋆ relation across the full mass range, which we argue is more physically relevant than the MGC-Mhalo relation. We also explore the physical processes driving the observed constant value of $\hbox{$M_{\rm GC}$}/ \hbox{$M_{\rm halo}$}\sim 5× 10^{-5}$ and find that it is the result of a combination of cluster formation physics and cluster disruption.